Geochemical and Isotopic Evidence for Provenance of the Western Sea of Japan Over the Last 30000 Years - Dou, Ruxi; Zou, Jianjun; Shi, Xuefa; Zhu, Aimei; Dong, Zhi; Gorbarenko, Sergey; He, Lianhua; Gao, Jingjing; Zhang, Ying; Cui, Jingjing (Frontiers in Earth Science, 2021)
The Sea of Japan, one of unique marginal seas of the western North Pacific, is characterized by high sill and thick sediments, which archives abundant information on variations in the East Asian Monsoon, Tsushima Warm Current, sea ice coverage, Westerly Jet, etc. In comparison with other marginal seas of the western North Pacific, the Sea of Japan is the only marginal sea without the influxes of big rivers at present. One of the most interesting scientific questions is to fingerprint the source of terrigenous sediments through time, especially in the western Sea of Japan, which is less investigated in previous report. In this study, a suite of multi-proxies including Sr and Nd isotopes and minor elements was measured for fine fractions of core LV53-18-2 recovered from the western Sea of Japan over the last 30 ka. Our results show that the sediments host abundant volcanic detritus and the provenance of terrigenous sediments in the western Sea of Japan are mainly derived from the arid region in the Northern China and coastal areas in the Far East. During the Last Glacial Maximum, the increased coverage of sea ice may contribute to the accumulation of terrigenous debris. On Meanwhile, the stronger East Asian Winter Monsoon and expansion of the Westerly Jet over the Northern China also carried more dust to the study area. However, the weakened atmospheric circulation and sea level rising induced by the ascending boreal insolation during the Last Deglaciation reduced input of terrigenous debris remarkably. After 8 ka, high stand sea level and opening of the Tatar Strait lead to the development of the Liman Cold Current, which transports large quantities of volcanic materials to study area continuously and produce more positive εNd and Eu anomaly and depleted ΣREE.